Основи та напрями реалізації політики ЄС у сфері розвитку цифрової економіки - Іванцов, С.В. (Управління економікою: теорія та практика, 2025)
Враховуючи, що розвиток цифрової економіки (ЦЕ) став одним з головних пріоритетів ЄС, він розпочав реалізацію наднаціональної політики у цій сфері, сприяючи цифровим трансформаціям різних галузей економіки та соціальної сфери. Метою роботи є узагальнення основ і дослідження напрямів реалізації політики ЄС у сфері розвитку цифрової економіки. Визначено основи стратегічного курсу ЄС щодо її розвитку та узагальнено основні передумови реалізації політики ЄС у цій сфері. Досліджено основні напрями політики розвитку цифрової економіки в ЄС, зокрема: формування єдиного простору даних, підвищення рівня кібербезпеки, розвиток цифрового сектору, цифровізацію єдиного внутрішнього ринку, сприяння цифровим трансформаціям у різних структурних сферах, цифрову трансформацію державних послуг та управління, соціальної сфери та громадянського простору. Обґрунтовано, що розвиток посилює системні властивості цифрової економіки ЄС. Окреслено європейський підхід до цифрових трансформацій та міжнародно-регіональні особливості розвитку цифрової економіки у ЄС. In recent years, digital transformations (DT) have become the most important factor in economic dynamics and growth and also lay the foundation for the future long economic cycle. In view of this, the digital economy (DE) development, the so-called digital transition, is one of the most significant strategic tasks that the EU has set for itself. Also, this organisation moved to the implementation of a joint supranational policy in the field of DE development. Therefore, the goal of the work is to generalise the basics and to study the directions of EU policy implementation in the field of DE development. The foundations of the EU’s strategic course on the DE development are defined and the main prerequisites for the implementation of the EU’s policy on the DE development are summarized, namely: broad communication and cooperation of all participants and stakeholders, the basis for which is the supranational EU system; financial support of DT from the ESM; technical, expert and other assistance to member countries. Forms of financial support for DT from the EU, as well as multinational projects as a legal instrument for supporting in-depth cooperation of member states in the digital sphere, are separately characterised. The main policy directions of the DE development in the EU were studied, in particular: the formation of a single data space, raising the level of cyber security, the development of the digital sector, the digitalization of the single internal market, the promotion of DT in various structural spheres, the digital transformation of public services and management, the social sphere and civil space. It is demonstrated that the development strengthens the systemic properties of the EU DE. The European approach to DT and international and regional characteristics of DE development in the EU are outlined.